Percepción sobre la depresión en los estudiantes de una Institución Educativa en el municipio de Dibulla La Guajira (2024)
The present research focused on identifying the perception of adolescents about depression in an educational institution in the municipality of Dibulla, La Guajira. The objective of the study was to describe the perception of adolescent students about depression at the Nuestra Señora del Pilar educational institution in Dibulla La Guajira. To fully carry out this study, a qualitative methodology based on semi-structured interviews was used. To represent the target population, 6 adolescent high school students were chosen, one student for each grade, so that in their own words they could narrate what depression means to them, identifying the causes, symptoms and treatments from their experiences. It is very clear that they have a lot of misinformation regarding depression as a disorder, but they associate it with certain factors of sadness, absences and self-harm that are accompanied by deep crying and discouragement. On the other hand, it can be stated that depression does not know the social background or ages, much less the socio-emotional conditions that allow us to cope in the best way and prevent this disorder. B